2001
DOI: 10.1155/2001/75780
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Series Resistances and Mobility Attenuation Phenomena in Short Channel MOS Transistors

Abstract: As the scaling proceeds, the transverse electric field increase, and a mobility attenuation phenomenon becomes of primordial interest. Indeed, the high transverse electric field is generally ascribed [1] to surface roughness scattering in the channel and consequently reduce effective mobility of carriers. In short channel MOSFET, the Source-Drain resistance Rsa influence strongly the effective mobility. The aim of this work is therefore to propose an original method especially conceived for the extraction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…A lot of methods have been proposed for the MOSFET parameter extraction but they are generally restricted to the above threshold region and mostly assume that the inversion charge varies linearly with gate voltage overdrive [1][2][3][4][5][6][7][8][9][10][11]. As the supply voltage Vdd is reduced with device scaling, the operating gate bias moves closer to the threshold voltage (near threshold operation), and the assumption that the inversion charge varies approximately linearly with gate voltage overdrive becomes less and less accurate.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of methods have been proposed for the MOSFET parameter extraction but they are generally restricted to the above threshold region and mostly assume that the inversion charge varies linearly with gate voltage overdrive [1][2][3][4][5][6][7][8][9][10][11]. As the supply voltage Vdd is reduced with device scaling, the operating gate bias moves closer to the threshold voltage (near threshold operation), and the assumption that the inversion charge varies approximately linearly with gate voltage overdrive becomes less and less accurate.…”
Section: Introductionmentioning
confidence: 99%
“…This is easily obtained at low temperature. For room temperature, we can neglect a coulomb proportional factor and use the method described in the previous works [6]. The coulomb proportional factor ␣ increase slightly between helium temperature to 77 K and decrease after this temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, It was shown that the scattering mechanism at room temperature is essentially the surface roughness, it was described by the exponential model [5,6]. This model assume that the mobility is null in few angstroms in the vicinity of the interface Si/oxide, and explain the negative trans-conductance observed at high field.…”
Section: Introductionmentioning
confidence: 99%
“…According to the classical model [10], and for low fields, the comparison of the first-order development of the exponential term in relation (3) gives the relation between the intrinsic coefficient attenuation mobility in exponential model and its value extrinsic θ e in the classical model:…”
Section: First Methodsmentioning
confidence: 99%
“…The model of variation mobility with effective field considers that the attenuation of effective mobility is particularly due to Surface Roughness Scattering [10]. This work generalized all the classical models [9,11] and give a physical meaning to the different used parameters.…”
Section: Active and Passive Electronic Componentsmentioning
confidence: 99%